The birth of a nation : the early years of the United States - Faber, Doris, 1924-; Faber, Harold (New York : Scribner, 1989)
Examines the important events and figures involved in the first few years of the new American nation, from the organization of the first federal government to the election of John Adams as the second president.
Includes index.
Bibliography: p. 189-190.
Keywords: United States -- Politics and government -- 1789-1797 -- Juvenile literature; United States -- Politics and government -- 1789-1797.